2018
DOI: 10.33371/ijoc.v12i2.578
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Liver Cancer in Isfahan Province, Iran

Abstract: Background: Liver cancer remains to grow worldwide. We aimed to describe the period prevalence (PP) and incidence rates (Irs) for liver cancer in Isfahan Province that is located in the center of Iran and ranked as the third province in terms of population.Methods: Information related to the Surveillance, Epidemiology, and End Results; (SEER) was collected from the Isfahan Cancer Registry. Period prevalence (PP) was calculated per 100,000 people. The cancer sites studied were defined according to the Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…In the 71% of the population studied in here, the highest incidence of CNS tumors was found in the age between 20 and 70 years old. This is in agreement with previous publication which confirms an incidence in most CNS tumors with age until the seventh decade [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 93%
“…In the 71% of the population studied in here, the highest incidence of CNS tumors was found in the age between 20 and 70 years old. This is in agreement with previous publication which confirms an incidence in most CNS tumors with age until the seventh decade [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed that urinary bladder, kidney cancer followed an increasing trend in incidence, mortality and prevalence in Isfahan, Iran (14)(15)(16)(17)(18)(19)(20)(26)(27)(28)(29)(30)(31)(32). The implications of this investigation could be mentioned as the following suggestions: (1) the health care system should provide a model-based strategy to improve access to specialized medical, pharmacological and surgical facilities; (2) consideration is needed toward the reality for scheduling health system improvements, particularly referral systems; (3) preventing significant difficulties by equality of management for patient satisfaction; (4) attention toward financial management by study of epidemiology and pharmacotherapy.…”
Section: Discussionmentioning
confidence: 83%
“…CRC is the main cause of morbidity and mortality in which was reported as the third deadliest cancer throughout the world (1). Due to Western influences of lifestyle in many countries, including Iran, the study of CRC is an important issue for health authorities (14)(15)(16)(17)(18)(19). The mean age of patients in this study was 62.0 year with a tendency associated with 82% of occurrence in older age of life (50 to 98 years).…”
Section: Discussionmentioning
confidence: 85%